KAJIAN GASTRONOMI MIE CELOR SEBAGAI MAKANAN KHAS PALEMBANG - Clara Augustin Chang; Yudhiet Fajar Dewantara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Em This study aims to examine the role of gastronomic components in traditional mie celor noodles as a representation of Palembang's unique culinary culture. The issues raised are the low recognition of mie celor outside its region of origin and the limited preservation of its gastronomic value. This study employs a descriptive qualitative approach with data collection methods including in-depth interviews, observations, and documentation. The informants in this study consist of nine stakeholders (Nona Helix) representing business operators, visitors, suppliers, culinary experts, academics, and government officials. Data was analyzed using the Miles and Huberman model (data reduction, data presentation, and verification), supported by the NVivo application for keyword frequency mapping. The study found that mie celor possesses high gastronomic value across nine aspects: raw materials, cooking techniques, tasting, presentation, dining etiquette, dining experience, nutrition, history, and preservation. Words such as “noodles,” “celor,” “Palembang,” “shrimp,” “coconut milk,” and “culture” dominate the keyword frequency in the data, reflecting the strong connection between this dish and local cultural identity. The research findings also indicate that mie celor plays a role in strengthening Palembang’s culinary identity, but it has not yet been integrated into educational or promotional programs. Therefore, collaboration between the government, businesses, and educational institutions is needed to develop a cultural heritage-based culinary preservation program.